Formulasi Pembelajaran Hadis Digital: (Studi Kasus di UIN Sultan Maulana Hasanuddin Banten) - Hidayah, Ilhamiyatul; Nurlaeli, Puput; Romadhony, Nagib; Ihksan, Ahmad; Arifin, Azis (Jurnal Penelitian Ilmu Ushuluddin, 2025)
Technology has become important in education in Indonesia, especially in digital learning that offers opportunities to improve the quality of teaching and learning. Digital hadith applications emerge as a significant innovation that not only facilitates accessibility to hadith texts that have been studied conventionally but also expands the range of understanding and practice of Islamic teachings through various digital platforms, thus encouraging students to be more active in seeking and learning religious knowledge independently and responsive to the dynamics of the times. The purpose of this study is to see how the process of implementing hadith learning into a digital model makes it easier for students to access. The method used in the research is a qualitative approach with data collection techniques in the form of interviews and questionnaires. From the research results, many students feel helped by the existence of digital hadith because it makes it easier for them to find references, increases understanding in learning hadith, and eases access that can be done anytime and anywhere. Thus, digital hadith has a very significant impact on helping the student learning process. The author suggests that the scope of research variables be further expanded to provide a more comprehensive picture for future research.